Predictors of healthcare mistreatment among transgender and gender diverse individuals: Are there different patterns by patient race and ethnicity?. (28th May 2021) - Seelman, Kristie L.; Vasi, Andre; Kattari, Shanna K.; Alvarez-Hernandez, Luis R.
ABSTRACT: Using data from the 2015 United States Transgender Survey, this study investigates which patient sociodemographic characteristics and psychosocial risks are associated with likelihood of transgender mistreatment in healthcare and how patterns vary for patients of color. Numerous predictors, including alignment of identity documents, were associated with healthcare mistreatment. Among subgroups of transgender patients of color, psychosocial risks were more consistently significant than sociodemographic characteristics in predicting mistreatment. National and international health organizations are called to enact clear policies that affirm transgender patients and patients of color and establish a commitment to effectively serving these populations within their ethical codes.